Meningkatkan Kinerja Non-Keuangan Melalui Pengelolaan Sumber Daya Manusia dan Manajemen Pengetahuan yang Efektif pada PT. Bank SulutGo Cabang Gorontalo - Zelfitriana Isra; Heldy Vanni Alam; Rezkiawan Tantawi (MES Bogor, 2024)
This research aims to determine the influence of human resource management and knowledge management on non-financial performance at PT. Bank SulutGo Gorontalo Branch. The research applies total sampling involving 43 respondents.The data collection technique employed in the research is questionnaires distributed to all employees at PT. Bank SulutGo Branch. The analytical tool used to test this research is Multiple Linier Regression with analysis aided by Statistical Program for Social Science ( SPSS) Version 26. The result indicate that, partially, human resource management significant influence on non-financial performance. Simultaneously, both human resource management and knowledge management significantly influence non-financial performance at PT. Bank SulutGo Gorontalo Branch.